Molecular Phylogenetics and Taxonomy of the Andean Genus Lynchius Hedges, Duellman, and Heinicke 2008 (Anura: Craugastoridae) - Motta, Ana P. [UNESP]; Chaparro, Juan C.; Pombal, Jose P.; Guayasamin, Juan M.; De la Riva, Ignacio; Padial, Jose M. (Herpetologists League, 2016)
We infer species relationships within Lynchius, a frog genus with four species distributed along the paramos and cloud forests of the Andes of northern Peru and southern Ecuador, and assess species diversity in light of comparative analyses of anatomical traits and inferred relationships. Phylogenetic analyses rely on similar to 7000 base pairs of mtDNA and nuDNA sequences aligned using similarity-alignment and tree-alignment and optimized under maximum likelihood and parsimony criteria. Inferred relationships place Lynchius as the sister group of the widespread genus Oreobates and this clade as the sister group of the high Andean genus Phrynopus. Our analyses corroborate the dissimilar species Lynchius simmonsi as part of this clade and place it as the sister group of the remaining species of Lynchius. Parsimony and maximum likelihood analyses differ in the internal relationships of Lynchius with respect to the placement of L. flavomaculatus, L. nebulanastes, and L. parkeri, but support the existence of two unnamed species. External morphological comparisons provide diagnostic characters for the two new species, which are named and described herein. Lynchius tabaconas is sister to L. flavomaculatus and occurs at similar to 2800 m in the cloud forests of Santuario Nacional Tabaconas-Namballe, Cajamarca, Peru. Lynchius oblitus occurs in the same area but at a higher elevation (similar to 3300 m) and is sister to a clade formed by L. flavomaculatus and L. tabaconas in parsimony analyses and to L. nebulanastes in maximum likelihood analyses. We provide a new diagnosis for each of the six species and for the genus, as well as some natural history notes.
Keywords: Brachycephaloidea; Lynchius oblitus sp nov.; Lynchius tabaconas sp nov.; Oreobates; Paramo; Phrynopus; Terrarana